2015
DOI: 10.1016/j.csbj.2015.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Genome mining: Prediction of lipopeptides and polyketides from Bacillus and related Firmicutes

Abstract: Bacillus and related genera in the Bacillales within the Firmicutes harbor a variety of secondary metabolite gene clusters encoding polyketide synthases and non-ribosomal peptide synthetases responsible for remarkable diverse number of polyketides (PKs) and lipopeptides (LPs). These compounds may be utilized for medical and agricultural applications. Here, we summarize the knowledge on structural diversity and underlying gene clusters of LPs and PKs in the Bacillales. Moreover, we evaluate by using published p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
137
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(140 citation statements)
references
References 84 publications
3
137
0
Order By: Relevance
“…Among them, NRPs produced by Bacillales include lipopeptides (LPs) and others, with significant antimicrobial activity [136]. Here we present an extended collection based on members described in a previous review by Aleti et al [136]. By use of antiSMASH, we identified 31 types of putative NRPs, PKs and NRPS/PKS hybrid synthesized antimicrobials, which will be described in detail below.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among them, NRPs produced by Bacillales include lipopeptides (LPs) and others, with significant antimicrobial activity [136]. Here we present an extended collection based on members described in a previous review by Aleti et al [136]. By use of antiSMASH, we identified 31 types of putative NRPs, PKs and NRPS/PKS hybrid synthesized antimicrobials, which will be described in detail below.…”
Section: Resultsmentioning
confidence: 99%
“…are likely to be the main producers of LPs, which are mainly known for their antifungal properties [138–140]. Based on a previous genome mining work (see review Aleti et al [136]), we identified locillomycins as novel members of LPs in species of Bacillales (Additional file 3: Table S3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The product homologues and specific applications of top lipopeptide-elaborating bacteria Bacillus and Paenibacillus spp. been reviewed in many insightful reviews Aleti et al 2015). The synergistic effect of lipopeptides with colistin (polymyxin E) in inhibition of multidrug-resistant (MDR) Acinetobacter baumannii has been reviewed (Claeys et al 2014).…”
Section: Introductionmentioning
confidence: 98%